The Mechanism of Heat Stress Resistance During Spermatogenesis in Turpan Black Sheep - Song, Yukun; Zhao, Xi; Aihemaiti, Aikebaier; Haire, Aerman; Gao, Yu; Niu, Chao; Yang, Peng; Liu, Guoshi; Jia, Gongxue; Wusiman, Abulizi (Frontiers in Veterinary Science, 2022)
Heat stress can affect the reproductive function of livestock and bring harm to animal production, which can seriously damage the economic interests of livestock producers. Therefore, it is important to explore deeper the effect of heat stress on the reproductive function to improve livestock production. In this study, the experimental animals Turpan black sheep and Suffolk sheep were selected as controls, each with 10 sheep, and the reproductive physiological performance was measured in Turpan, China from April to August when there was no heat stress to strong heat stress. The results showed that the sperm density, vitality, and kinematic parameters of Suffolk sheep were significantly lower than that in Turpan black sheep (P<0.01) after heat stress, while the sperm acrosome malfunctions and DNA damage was significantly higher in Suffolk sheep (P <0.01). In addition, the endogenous levels of reproductive hormones and oxidative stress indicators in the blood of Turpan black sheep were stable before and after heat stress treatment, while Suffolk sheep showed different degrees of fluctuations. There was no significant difference in testicular histomorphology between the two after heat stress treatment. However, Suffolk sheep showed a significantly decreased number of spermatocytes after heat stress treatment (P<0.05). It was found in the meiosis exhibit that the proportion of cells in the meiotic zygotene stage of Suffolk sheep was significantly higher than that of Turpan black sheep. To investigate the mechanism of normal spermatogenesis in Turpan black sheep under heat stress, we performed RNA-Seq analysis on testis. The results showed that there were 3559 differential genes in Turpan black sheep before and after heat stress, with 2118 up-regulated genes and 1,441 down-regulated genes. The enrichment analysis of GO and KEGG showed that the differential genes are mainly involved in cellular component organization or biogenesis, cell cycle process, mitotic cell cycle process, meiotic cell cycle process, double-strand break repair and Rap1 signaling pathway, Ras signaling pathway, Cell cycle, signaling pathways regulating pluripotency of stem cells Oocyte meiosis.